Sistema para detecção, localização e monitoramento de descargas parciais em estatores de hidrogeradores - VILHENA, Paulo Roberto Moutinho de (Universidade Federal do Pará, 2017)
Stops machines unplanned caused by faults in the electrical insulation of the power electric system equipment is a big problem, because account for high losses to plan and undertake performance indicators due long stop period generating unit necessary for the generation function restoration. In order to solve this problem, many researchers and scholars in the field of large rotating machines found that these failures were often related to the increased level of partial discharges (PDs) of electrical insulation of the machine. Occurrences of PDs in insulating systems of high voltage equipment are symptoms of weakness in their dielectric withstand, whose evolution can cause serious consequences for the equipment. Because of these consequences, the evaluation of the operating status of the stator winding through the on line PDs measurement system proposed in this thesis presents strategies to increase the reliability of the measurements. As PDs sensor, it has been suggested to use electromagnetic microstrip directional coupler can detect the signal with the highest bandwidth in the UHF band, compared to existing traditional sensors. The development and implementation of virtual simulator PDs caused by the need of having Examples of signals that allow testing some PDs signal processing techniques. The main result of this thesis is the DP measurement system (called SIM_DP) including sensor, data acquisition system, PDs signal processing software and analysis of results. By studying the propagation of the signal in a stator bar was possible to develop a new methodology based on spectral analysis for PDs location. Through the structure created in the laboratory, it was possible to validate the SIM_DP system which favored the review of the PDs phenomenon. Finally actual data were analyzed for DP measurements in the field and correlation of PDs with mechanical vibration. The results of the work contributed to a more accurate diagnosis of the phenomenon. The results of the thesis have been improved in laboratory and field producing new: implementation of new laboratory tests as Voltage Endurance Test (VET), new non-invasive sensors such as antennas capable of measuring partial discharges and new techniques used in the analysis and diagnosis of related DP phenomena which will be presented in future work.